2011
DOI: 10.1159/000331278
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Elastic Tissue of the Human Aorta

Abstract: Background: Age-related arterial alterations affecting cells, matrix and biomolecules are the main culprit for initiation and progression of cardiovascular disease. The objective of this study is to gain further insights into the complex mechanism of elastic tissue ageing in human aortic blood vessels. Methods: One hundred and nineteen human aortic tissue samples were collected from adult patients (101 males, 18 females; age 40–86 years) undergoing coronary artery bypass grafting. Overall extracellular matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 87 publications
3
71
0
1
Order By: Relevance
“…by results obtained in a study on aortic punch biopsies similar to the ones used in this work, which revealed a decrease of the amount of interlaminar elastin and a decrease of tropoelastin mRNA levels with increased age, respectively [Fritze et al, 2011]. The similarities in the amounts of elastin found between aortic samples from WBS patients and healthy subjects may also be associated with an increase of the number of the elastic lamellae [O'Connor et al, 1985;Li et al, 1998], which may partly compensate for the lower amounts of elastin that are produced.…”
Section: Heinz Et Al 1837supporting
confidence: 70%
“…by results obtained in a study on aortic punch biopsies similar to the ones used in this work, which revealed a decrease of the amount of interlaminar elastin and a decrease of tropoelastin mRNA levels with increased age, respectively [Fritze et al, 2011]. The similarities in the amounts of elastin found between aortic samples from WBS patients and healthy subjects may also be associated with an increase of the number of the elastic lamellae [O'Connor et al, 1985;Li et al, 1998], which may partly compensate for the lower amounts of elastin that are produced.…”
Section: Heinz Et Al 1837supporting
confidence: 70%
“…Endothelial dysfunction may be due to diminished bioavailability of nitric oxide (Taddei et al, 2001; Tschudi et al, 1996). Arterial stiffness results primarily from loss of elastic fibers and an increase in collagen (Fritze et al, 2012). Like AD, cardiovascular disease is another aging‐related disease that brings a great burden for the patients and healthcare systems (Paneni, Diaz Cañestro, Libby, Lüscher, & Camici, 2017).…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%
“…In addition to MCP-1, numerous studies have reported increased MMP expression and activity in the ageing vascular wall which may also facilitate increased VSMC migration. Specifically, MMP-13 [36], MMP-9 [10,37] and MMP-2 expression and activity were elevated in the ageing vascular wall [10,12,13,36,37]. It has been proposed that increased MMP-2 activation is due to a combination of elevated levels of the MMP-2 activator MMP-14 and reduced levels of tissue inhibitor of metalloproteinase-2 in the ageing intima [13].…”
Section: Ageing and Vsmc Migrationmentioning
confidence: 99%